Perancangan Dan Implementasi Aplikasi Pembelajaran Membaca Dan Berhitung Untuk Anak Usia Dini Berbasis Android - Yulius Dani Eko Saputro; Stephanus Surijadarma Tandjung (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2023)
The current trend in the world of education is from traditional education to modern education using new information technology. The author designed a learning media application for children so that they can improve and develop their learning abilities. By making this application, parents can guide them in learning. The aim of this research is to design an application to improve learning abilities using the Waterfall Method. The Waterfall method is a sequential software development approach, with a process that runs sequentially from stage to stage, through the Requirements, Design, Implementation, Verification and Maintenance phases. The results obtained are the creation of an Android-based reading and arithmetic learning media application, where this application consists of several interesting features that can help children aged 4-9 years. The features in this application are packed with simple calculations, reading letters, and number recognition. To measure the application that is built as suitable for use, it is done by testing the application on 20 respondents and each respondent fills out a questionnaire consisting of 10 questions. Based on the results of the data analysis, a score of 78.625 was obtained, which means this application is suitable for use by children both in terms of appearance and content.